(untitled) (Journal of Nepal Geological Society, 2000)
The population to be resettled from the Three Gorges Reservoir of the Yangtze River is about 1.2 million. During the first period of the Project from 1993 to 1997, about 82 thousand people were resettled; whereas about 550 thousand will be resettled during the second period of the Project from 1997 to 2003, and over 600 thousand will be resettled during the third period of the Project by 2009. Resettlement is a great challenge, since in the vicinity of the reservoir, there is not much land suitable for constructing buildings and the area is subject to various geological hazards. The paper discusses the engineering geology of the area, especially the geological hazards and their control for resettlement. The control measures for major geological hazards that have a possibility of disrupting the navigation through the Yangtze River (such as the Lianziya hazardous rock mass, the Huanglashi Landslide. and Jiguanling Rockfall) are discussed in this paper. The geological hazard prevention projects undertaken for the resettlement in the new sites (such as Waxian, Wushan, and Badong) is also described.